Using Smartphone for Measuring the Magnetic Field Produced by the Current Flow in a Single Straight Line - Vongvizay, Pathom; Udomsamuthirun, Pongkaew; Ruangrungrote, Siriluck; Nilkamjon, Tunyanop; Kruaehong , Thitipong; Meakniti, Suppanyou (Journal of Advanced Development in Engineering and Science, 2024)
In this study, we design and build an experimental kit to use a smartphone to measure magnetic fields in accordance with Ampere's Law. The Phyphox application was used to measure the magnetic field created by a single straight-line current flow. We provide a method for removing the noise from the other electrical equipment in our experiment as well as the Earth's magnetic field. Air has a permeability of about 1.164 - 1.233 x10-6 N A-2.